Enterprise education in undergraduate business programmes advances students' negotiating competence and self-confidence - Enstroem, Rickard; Benson, Lyle (My University, 2024)
Purpose Business graduates’ enterprising capability augments their work readiness, transforming them into professionals capable of driving successful outcomes. At the core lie self-confidence and negotiating competence. However, embedding enterprise education and developing assessments to evidence learning is challenging. This study aims to offer a blueprint for establishing enterprise learning in the classroom and investigating the effectiveness of cultivating negotiating competence and self-confidence. Design/methodology/approach Modelled on Kolb’s experiential learning cycle, students engage in in-class and real-life negotiations, assessing self-confidence using a scale founded in Bandura’s self-efficacy theory. Open-ended reflections are also submitted. Quantitative data is analysed through multiple linear regression, while quantitative and qualitative data triangulation substantiates enterprise learning in negotiating competence and self-confidence. Findings Students’ reflections show that low self-confidence poses an initial barrier in negotiations, overcome with successive engagements. Quantitative analysis uncovers response-shift biases, with female and male students overestimating initial self-confidence levels. The gender and difference score type interaction reveals a more pronounced bias among female students starting from a lower baseline than male students, implying a more substantial self-confidence improvement for female students. These findings challenge traditional assumptions about gender differences in negotiations and emphasize the need for nuanced perspectives. Originality/value Enterprising capability is pivotal for business professionals. This study highlights the advancement of negotiating competence and self-confidence. It contributes uniquely to the development of enterprise education pedagogy. Focusing on nuanced gender differences challenges prevailing assumptions, providing a perspective to the discourse on negotiating competence and self-confidence in management training.
Keywords: enterprising; business; undergraduate; self-confidence; negotiations; transversal competencies